Quality of life after sialendoscopy: prospective non-randomized study - Giulianno Molina Melo; Murilo Catafesta Neves; Marcello Rosano; Christiana Maria Ribeiro Salles Vanni; Marcio Abrahao; Onivaldo Cervantes (BMC Surgery, 2022)
Abstract Background The symptomatic (swelling and pain) salivary gland obstructions are caused by sialolithiasis and salivary duct stenosis, negatively affecting quality of life (QOL), with almost all candidates for clinical measures and minimally invasive sialendoscopy. The impact of sialendoscopy treatment on the QOL has been little addressed nowadays. The objective is to prospectively evaluate the impact of sialendoscopy on the quality of life of patients undergoing sialendoscopy due to benign salivary obstructive diseases, measured through QOL questionnaires of xerostomia degree, the oral health impact profile and post sialendoscopy satisfaction questionnaires. Result 37 sialendoscopies were included, most young female; there were 64.5% sialolithiasis and 35.4% post-radioiodine; with 4.5 times/week painful swelling symptoms and 23.5 months symptom duration. The pre- and post-sialendoscopy VAS values were: 7.42 to 1.29 (p < 0.001); 86.5% and 89.2% were subjected to sialendoscopy alone and endoscopic dilatation respectively; 80.6% reported improved symptoms after sialendoscopy in the sialolithiasis clinic (p < 0.001). The physical pain and psychological discomfort domain scores were mostly impacted where sialendoscopy provided relief and improvement (p < 0.001). We found a positive correlation between sialendoscopy and obstructive stone disease (p < 0.001) and no correlation in sialendoscopy satisfaction in xerostomia patients (p = 0.009). Conclusions We found improved symptoms with overall good satisfaction after sialendoscopy correlated with stones; and a negative correlation between xerostomia. Our findings support the evident indication of sialendoscopy for obstructive sialolithiasis with a positive impact on QOL and probably a relative time-dependent indication for stenosis/other xerostomia causes that little improved QOL satisfaction. Level of evidence 2b—Prospective non-randomized study. Trial registration: WHO Universal Trial Number (UTN): U1111-1247-7028; Brazilian Clinical Trials Registry (ReBeC): RBR-6p8zfs.